MOTHER’S KNOWLEDGE AND ATTITUDE ABOUT STUNTING PREVENTION - Rini Kristiyanti; Rini Kristiyanti; Siti Khuzaiyah; Siti Khuzaiyah; Sandi Ari Susiatmi; Sandi Ari Susiatmi (Siklus : Journal Research Midwifery Politeknik Tegal, 2021)
Recently, stunting has becoming one of the nutritional problems experienced by toddlers in the world. Stunting will impact on children growth and development in the future. One of the factors related to stunting is mother’s knowledge. The objective of this study was to determine the factors related to the mother’s knowledge and attitude in preventing stunting. This was a cross-sectional study. The sample of this study was 50 pregnant women in Pekalongan Regency. This study showed that mother’s education significantly related to a mother’s knowledge (p-value: 0,017, Wald score: 5,687). On the other hand, the habit of food restriction strongly related to mother’s attitude in preventing stunting (p-value: 0,023, Wald score: 6,156). Further study with huge number of respondents is needed to gain more significant data. Moreover, health services should include education related to stunting and food restriction so that mothers could improve their knowledge and attitude in preventing stunting.